ΦΙΛ- NAMES AS CHARACTER DISPOSITION - Araújo, Carolina (Stylos, 2020)
The ancient Greek language was once alive, with a creative use of terms and the free formation of neologisms. Since Mycenaean times, the prefix φιλ- was employed to generate new words: proper and common names, adjectives and verbs, such as Philip, philanthropy, philharmonic and philosophize. This article begins by outlining the contemporary debate on these words, which locates Plato as a game changer in the development of their meaning. Next, it briefly addresses the so-called platonic love according to the alleged linguistic transposition it would have operated in the sense of the prefix φιλ-. The third section focuses on Plato’s account of the use and the formation of names in φιλ in the Republic and concludes that it is compatible with their traditional meaning. I show that these terms are neither norm-policing names referring to “wannabes”, nor do they designate a nostalgia towards an unreachable object. I conclude that φιλ- names have always denoted a type of obsession, and Plato’s analysis both clarifies their logic and adds a psychological theory to explain their common reference, namely, a specific disposition of character.